A cultura de segurança do paciente na perspectiva dos profissionais de saúde de um bloco cirúrgico - CAIXETA, Thaís Pereira (2017)
The safety culture of the patient is one of the strategies for promoting and strengthening actions that aim at the quality of health care and patient safety. The objective of this study was to understand the culture of patient safety from the perspective of health professionals. This is a descriptive-exploratory study of a qualitative nature, developed in a surgical center of an Education Hospital of interior of Minas Gerais. The data collection through a half structured interview with 97 health professionals, among them, nursing technicians, nurses and physicians. For an analysis of the data it was used the Content Analysis Method, following the following steps: pre-analysis, material exploration and treatment of results obtained and interpretation. The categories found after the analysis procedures were: Patient safety: to care for and protect their integrity; Factors that interfere in patient safety: aspects of (in) safety, Is the care provided to the patient in the surgical block safe? and Basic safety protocols: strategy to minimize damage to the patient. It was noticed that health professionals have mastery over the concept of patient safety, are able to identify factors that influence safety, as well as potentialities, fragilities and actions that should be implemented in the care to provide a patient care with greater safety. It was concluded that efforts should be prioritized by senior management and care professionals, with the aim of promoting the conditions that guarantee the safety culture in the hospital and the satisfaction of employees, patients and family members.